2013
DOI: 10.1111/fwb.12129
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of climatic–hydrological drivers on macroinvertebrate richness and composition in two Mediterranean streams

Abstract: Summary The unique information provided by multiyear data sets can aid in detecting major long‐term trends and making predictions with respect to environmental and biological variables. These trends are expected to differ among climatic regions but little information exists concerning long‐term variability within a particular climate region. We analysed the long‐term (14‐year time span) patterns in species richness and composition of aquatic insects (EPT: Ephemeroptera, Plecoptera and Trichoptera) in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 71 publications
3
19
1
Order By: Relevance
“…There are few datasets available that include more than 10 years of data, which are needed to detect long-term community changes (cf. [26,80,81]). Many of these datasets have been used to relate inter-annual community-changes to climate change, highlighting that the frequency of dry years has increased in more recent years and that communities have changed accordingly.…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few datasets available that include more than 10 years of data, which are needed to detect long-term community changes (cf. [26,80,81]). Many of these datasets have been used to relate inter-annual community-changes to climate change, highlighting that the frequency of dry years has increased in more recent years and that communities have changed accordingly.…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 99%
“…Many of these datasets have been used to relate inter-annual community-changes to climate change, highlighting that the frequency of dry years has increased in more recent years and that communities have changed accordingly. For example, Sáinz-Bariáin et al [82] found an increase in Trichoptera richness in high-altitude, mountain Mediterranean rivers after a 20-year period, whereas Pace et al [81] found that riffle species shifted to lentic species during a 14-year period in two Mediterranean streams with different hydrological characteristics. These patterns follow the hydrological changes experienced in these areas that may be the result of a changing climate.…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 99%
“…Lenat & Barbour, 1994;Hering et al, 2004;Larsen et al, 2012;Manfrin et al, 2013), and are frequently monitored to detect changes in hydrological and sediment regimes as well as in water quality of river in ecosystems (Boulton et al, 1992;Pace et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is widely recognised as having a profound impact on distribution of species (Pearson and Dawson ), modifying biodiversity patterns in terrestrial (Thuiller et al , Levinsky et al , Huntley et al , La Sorte and Jetz ), marine (Hiddink and ter Hofstede , Cheung et al , Albouy et al ) and fresh water (Buisson et al , Heino et al , Comte et al , Pace et al ) ecosystems. On ecological timescales, species assemblages are the result of a synergic interplay between colonisation and extirpation, two spatial‐ and temporal‐dependent processes influenced by regional and local drivers (He et al , Korhonen et al ).…”
mentioning
confidence: 99%